SS-BDD: Automated Acceptance Testing for Spreadsheets - Almeida, Lara; Cirilo, Elder; Barbosa, Eiji Adachi (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2016: Anais do I Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2016)
Current Spreadsheet Applications, such as Excel and Google Sheets, provide innumerous built-in facilities, including arithmetic, financial and statistical operations, as well as conditional expressions. Thus, users with little or no formal training in programming can use Spreadsheet Applications to implement their own Spreadsheet Programs. In fact, Spreadsheet Applications have become one of the most popular end-user programming environments nowadays. However, these applications also ease the introduction of errors in Spreadsheet Programs. Minor mistakes in formulas can mislead decisionmaking processes, resulting in uncountable costs to organizations. In general, end-user programmers are unaware of the potential risks that the uncontrolled construction of Spreadsheet Programs can cause. Therefore, a major focus of this paper is to offer an automated approach that makes programmers aware of introduced faults, so that they can build high quality Spreadsheet Programs. In particular, we propose SS-BDD, a framework for building and running Spreadsheets test scenarios, which relies on the use of Behavior Driven Development (BDD). We used SS-BDD to test three different Spreadsheet Programs. Our experience shows that SS-BDD can be used to build end-user friendly test scenarios which can achieve high fault-detection effectiveness.